Hubungan Pengetahuan Ibu Tentang KB Pasca Salin dengan Keikutsertaan Menjadi Akseptor KB di RSU Balimbingan Kota Pematang Siantar - Friany Martogi Gultom; Lasria Simamora; Tetti Seriati Situmorang; Mediana Beru Sembiring (Lembaga Pengembangan Kinerja Dosen, 2025)
In Indonesia, government attention to the use of post-saline contraceptives is increasing. According to the recommendations of The National Meeting on Family Planning Programs in 2012, the postpartum and post-miscarriage Family Planning (KB PP & PK) program is designated as a priority program that should be available in every province. This program aims not only to increase the number of contraceptive use, but also to improve maternal and child health (JNPK, 2012). Post-copy family planning is one of the government programs with a target of 80%, although the acceptor of post-copy family planning only reaches 30%, the Minister of Health of the Republic of Indonesia considers this achievement as a significant progress in increasing community participation in family planning programs. Meanwhile, the number of family planning acceptors in North Sumatra in 2012 reached 4,041 acceptors. This study aims to analyze the relationship between maternal knowledge about post-copy family planning and participation in becoming a family planning acceptor at Balimbingan Hospital, Tanah Jawa District, Simalungun Regency, Pematang Siantar City in 2024. This study applies an analytical survey method with a cross-sectional approach with sampling carried out using the Incidental Sampling technique of 44 people. The data analysis technique applied was Spearman's Rho Correlation with a significance level of 5% or a confidence level of 95%. The results of the study based on the output test statistics obtained the result of p=0.007 (<0.05). The conclusion of the study is that Ha is accepted, which means that maternal knowledge has a significant relationship with participation in becoming a post-copy family planning acceptor. It is hoped that the Family Planning program management officer at Balimbingan Hospital will continue to provide accurate information, education and counseling.